The Influence of Village-Owned Enterprises (BUMDes) on The Level of Welfare in Daenaa Village - Asni Bakari; Radia Hafid; Ivan Rahmad Santoso; Melizubaida Mahmud; Abdulrahim Maruwae (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to determine the influence of Village-Owned Enterprises (BUMDes) on the level of community welfare in Daenaa Village, West Limboto District, Gorontalo Province. BUMDes is one of the instruments of village economic development which is expected to be able to increase income and community welfare through the independent and sustainable management of village potential. The problem in this study is the extent of the influence of the existence and performance of BUMDes on the level of community welfare in Daenaa Village. The method used in this study is a quantitative method with a simple linear regression approach. The data used is primary data obtained through the distribution of questionnaires or questionnaires to respondents. The population in this study amounted to 758 people, while the sample used was 119 respondents determined by certain sampling techniques. The data was analyzed using a simple linear regression test to determine the relationship and influence of BUMDes variables on the level of community welfare. The results of the study show that there is an influence between Village-Owned Enterprises (BUMDes) on the level of community welfare in Daenaa Village. This is evidenced by the value of the Pearson correlation coefficient of 0.489 which shows a fairly strong relationship between the BUMDes variable and the level of community welfare. In addition, the remaining 0.511 was influenced by other variables that were not studied in this study. These findings show that the existence of BUMDes has an important role in improving people's welfare, although there are still other factors that also contribute to welfare.